INDO - GREEN TANK : INDONESIAN AGRICULTURE GENETIC BANK, SOLUSI DALAM INVENTARISASI, PEMANFAATAN DAN KONSERVASI SUMBERDAYA GENETIK SEBAGAI UPAYA PENDUKUNG KEDAULATAN PANGAN INDONESIA - Prasetyo, Rahmat Aji; Haryadi, Priyas; Hidayati, Anik Nur (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Food is a basic need of every human being, without any human food certainly will not be able to live. However, to meet food needs, Indonesia still have to import from other countries. Indonesia is a tropical country where natural resources are abundant. Most of the existing biodiversity in the world are in Indonesia. To meet the needs of food, one of which is to make plant breeding efforts. However, the plant breeding activities in Indonesia are still experiencing problems in the form of difficulty to get the genetic material that is key to getting high yielding varieties. This paper aims to formulate the formation of a special institution in charge of the inventory, use and conserve genetic resources in Indonesia. At present, genetic resources have not been managed and fully utilized by the government even though its potential is very large in Indonesia. Genetic resources are usually managed by different people so it is not integrated in a good koordinasiyang. INDO- GREEN TANK is an idea that institutions are expected to be the solution to deal with the food crisis in Indonesia in the future. Keywords: Genetic Bank, Conservation, Food Sovereignty